A perspective for rural development based on the dairy-farming production system in Iporá and surroundings, Goiás State - Dias, Kaique Moreira; Silva, Marisa Marques; Wander, Alcido Elenor; Salviano, Paulo Alexandre Perdomo; Carvalho, Eduardo Rodrigues de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2015)
The objective of this study was to characterize the dairy-farming production system in Iporá and adjacent municipalities. In the present work 257 interviews were conducted from April to November 2013 in several locations. Mean milk production per farm was 207.9 liters/day and dairy cow yield was 7.8 liters/day. The indicators of pasture degradation was high (n=111/63.8%). Natural breeding was more frequent (n=155/82.4%) than artificial insemination (n=33/17.6%). Milking cows manually was more frequent (n=146/82.9%) than mechanical milking (n=30/17.1%). The most predominant milking construction was the roofless shed with packed earth floor (n=98/63.2%). Milk quality may be reduced due to certain procedures adopted during milking (48 herdsmen dry the saliva of the calf on the teat surface with the cow tail, 63 herdsmen remove the saliva of the calf on the teat surface by hand and dry it on the cow coat, and 67 herdsmen remove the saliva of the calf on the teat surface by hand and dry it on their pants). Vaccination against leptospirosis, bovine viral diarrhea, infectious bovine rhinotracheitis and neosporosis was low (n=26, 24, 20 and 7, respectively). The dairy-farming production system in Iporá and surroundings needs improvements to increase milk production and create opportunities for rural development. Uma perspectiva de desenvolvimento rural baseada no sistema de produção de leite em Iporá e adjacências, Estado de Goiás Resumo: objetivou-se nesse estudo caracterizar o sistema de produção de leite em Iporá e municípios adjacentes. Realizaram-se 257 entrevistas entre abril e novembro de 2013 em diversos locais. A produção de leite por fazenda foi de 207,9 litros/dia e a produtividade/vaca foi de 7,8 litros/dia. Os indicadores de degradação de pastagens foram altos (n=111/63,8%). A monta natural foi mais frequente (n=155/82,4%) que a inseminação artificial (n=33/17,6%). A ordenha manual foi mais frequente (n=146/82,9%) que a mecânica (n=30/17,1%). O tipo de construção predominante foi o barracão descoberto com piso de chão batido (n=98/63,2%). A qualidade do leite pode ser reduzida devido a certos procedimentos adotados durante a ordenha (48 ordenhadores secam a saliva do bezerro na superfície do teto com o rabo da vaca, 63 ordenhadores removem a saliva do bezerro na superfície do teto com a mão e a seca no pelo da vaca, e 67 ordenhadores removem a saliva do bezerro na superfície do teto com a mão e a seca na calça). A vacinação contra leptospirose, diarreia viral bovina, rinotraqueíte infecciosa bovina e neosporose foi baixa (n= 26, 24, 20 e 7, respectivamente). O sistema de produção em Iporá e municípios adjacentes necessita de melhorias para aumento na produção de leite e oportunidades de desenvolvimento rural.